Target frames in British hotel websites - Fuster-Márquez, Miguel; Pennock-Speck, Barry (International Journal of English Studies, 2015)
This article centres on four-word phrase frames in British hospitality websites. Our aim is to identify those frames that are specific to this website genre, which we call target frames. Each phrase frame represents an identical sequence of words except for one variable word, that is A*BC or AB*D. The words that fill the slot, marked with an asterisk, are called fillers. We used a corpus-driven approach using KfNgram software to identify the phrase frames in our corpus (COMETVAL). We regard phrase frames as genre-specific when they are significantly more frequent than those found in the written section of the BNC, which represents General British English. We further filtered our selection of phrase frames by eliminating those which were not semantically homogenous with regard to the variable words they contained. Only in this way could the 76 phrase frames we identified be classified according to their primary discourse function. We contend that our study is a valuable addition to the literature on phraseology and can be of use in pedagogical and professional settings.